Patient‐rated impulsivity and aggression compared with clinician‐rated risk in a forensic psychiatric sample: Predicting inpatient incidents. (30th October 2019) - Karsten, Julie; Akkerman‐Bouwsema, Gerjonne J.; Hagenauw, Loes A.; Gerlsma, Coby; Lancel, Marike
Abstract: Background: Measures of impulsivity and aggression help to indicate risk of future violence or rule‐breaking. Both clinician‐rated risk assessment and self‐report measures have been used but hardly ever compared in their ability to predict inpatient incidents. Aims: To compare the self‐report on the Barratt Impulsiveness Scale (BIS‐11) and Buss‐Perry Aggression Questionnaire (BPAQ) with the clinician‐rated HKT‐30, a Dutch adaptation of the Historical Clinical Risk Management‐20, for their capacity to predict inpatient incidents. Methods: All men newly admitted to a forensic psychiatric hospital were invited to participate in this study unless in intensive care. Tests of correlation were run between the BIS‐11 and BPAQ scale scores and the HKT‐30. Each was then tested separately for capacity to predict the number of aggressive and nonaggressive incidents while resident. Finally, scores of all rating scales were entered together into a negative binomial regression to compare their relative strengths in predicting later incidents. Results: Patient and staff baseline impulsivity and aggression ratings correlated moderately well. All measures performed well in univariate analyses of relationship between baseline measures and later incidents. In final models, which included both patient and staff baseline ratings, the HKT‐30 generally outperformed the self‐report measures in the prediction of aggressive and nonaggressive incidents in both the first year and total length of stay. Implications for clinical practice: Our findings suggest that some reliance may be placed on patient ratings of their own propensity for impulsive and/or violent acts, but, when used, they should remain combined with clinician‐rated risk assessment for the time being. Future research should explore their utility in dialogue about treatment, and also the relative strength of staff response to each.